Markers of T Cell Exhaustion and Senescence and Their Relationship to Plasma TGF-β Levels in Treated HIV+ Immune Non-responders - Shive, Carey L.; Freeman, Michael L.; Younes, Souheil-Antoine; Kowal, Corinne M.; Canaday, David H.; Rodriguez, Benigno; Lederman, Michael M.; Anthony, Donald D. (Frontiers in Immunology, 2021)
Background: Immune non-responders (INR) are HIV+, ART-controlled (>2 yrs) people who fail to reconstitute their CD4 T cell numbers. Systemic inflammation and markers of T cell senescence and exhaustion are observed in INR. This study aims to investigate T cell senescence and exhaustion and their possible association with soluble immune mediators and to understand the immune profile of HIV-infected INR. Selected participants were <50 years old to control for the confounder of older age. Methods: Plasma levels of IL-6, IP10, sCD14, sCD163, and TGF-β and markers of T cell exhaustion (PD-1, TIGIT) and senescence (CD57, KLRG-1) were measured in ART-treated, HIV+ participants grouped by CD4 T cell counts (n = 63). Immune parameters were also measured in HIV-uninfected, age distribution-matched controls (HC; n = 30). Associations between T cell markers of exhaustion and senescence and plasma levels of immune mediators were examined by Spearman rank order statistics. Results: Proportions of CD4 T cell subsets expressing markers of exhaustion (PD-1, TIGIT) and senescence (CD57, KLRG-1) were elevated in HIV+ participants. When comparing proportions between INR and IR, INR had higher proportions of CD4 memory PD-1+, EM CD57+, TEM TIGIT+ and CD8 EM and TEM TIGIT+ cells. Plasma levels of IL-6, IP10, and sCD14 were elevated during HIV infection. IP10 was higher in INR. Plasma TGF-β levels and CD4 cycling proportions of T regulatory cells were lower in INR. Proportions of CD4 T cells expressing TIGIT, PD-1, and CD57 positively correlated with plasma levels of IL-6. Plasma levels of TGF-β negatively correlated with proportions of TIGIT+ and PD-1+ T cell subsets. Conclusions: INR have lower levels of TGF-β and decreased proportions of cycling CD4 T regulatory cells and may have difficulty controlling inflammation. IP10 is elevated in INR and is linked to higher proportions of T cell exhaustion and senescence seen in INR.